Hydrothermal synthesis of TiO2 nanosheets photoelectrocatalyst on Ti mesh for degradation of norfloxacin: Influence of pickling agents. (1st March 2016) - Zhang, Xiaoyun; Li, Dong; Wan, Jiafeng; Yu, Xiujuan
Abstract: TiO2 nanosheets (TiO2 -NSs) photoanodes were synthesized on the surface of Ti meshes via the hydrothermal method, and then washed by HCl, HNO3 and H3 PO4, respectively. The TiO2 -NSs washed by different pickling agents were characterized by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), scanning electrons microscopy (SEM), and UV–vis diffuse reflectance spectra (DRS). The results showed that P and N were transferred into the lattice of TiO2 . The TiO2 -NSs samples washed by HCl and HNO3 both had a mixture of anatase and rutile structures, while the TiO2 -NSs washed by H3 PO4 only contained anatase phase. It could be concluded that H3 PO4 pickling inhibited the formation of rutile phase. Moreover, TiO2 -NSs washed by HNO3 (TiO2 -NSs-HNO3 ) exhibited the strongest light absorption ability in visible region. Photoelectrochemical properties of the TiO2 -NSs photoelectrodes washed by different agents were investigated via transient photocurrent response (TPR), open-circuit potential (OCP) and electrochemical impedance spectroscopy (EIS). The photocatalytic (PC) and photoelectrocatalytic (PEC) performances were evaluated by the degradation of norfloxacin and the yield of OH radicals in the reactors. The results showed that the TiO2 -NSs-HNO3 photoelectrode revealed the highest photoinduced current of 1.08 mA/cm 2, open-circuit photovoltage of −0.22 V, PEC efficiency of 93% for the removal of norfloxacin. In addition, the enhanced PEC mechanism for TiO2 -NSs-HNO3 was proposed. The high PEC activity of TiO2 -NSs-HNO3 could be attributed to the introduction of N during acid-washing procedure, which could not only reduce the band gap energy but also accelerate the separation and transportation of photogenerated charge carriers.